Sorafenib induces ferroptosis in human renal cell carcinoma cells through CCAT/enhancer-binding protein homologous protein - Dinh Thi Nhung; Obadah E.A. Yousif; Byungsuk Kwon (Biochemistry and Biophysics Reports, 2025)
Sorafenib, a multi-kinase inhibitor, has been shown to induce ferroptosis, a form of lipid peroxidation-mediated cell death. However, a mechanism of how sorafenib-induced ER stress leads to ferroptosis remains unclear. Here, we report that the CCAT/enhancer-binding protein (C/EBP) homologous protein (CHOP) is a critical mediator linking ER stress to ferroptosis in human renal cell carcinoma (RCC) cells after exposure to sorafenib. A large portion of sorafenib-induced cell death was shown to be caused by ferroptosis and ER stress significantly contributed to this ferroptic cell death. Among three major ER stress pathways, sorafenib specifically induced activation of the ATF4-CHOP axis. CHOP in turn functioned as an effector suppressing expression of SLC7A11. Therefore, our results suggest that sorafenib induces ferroptosis in RCC cells by increasing uncontrolled oxidative stress.